Web-based learning media assisted by powtoon in basic mathematics course - Susanti, Vera Dewi; Andari, Tri; Harenza, Angga (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
In basic mathematics learning, lecturers used an LCD projector and taught it classically so that learning becomes uninteresting. Consequently, students become less enthusiastic and less interested. In overcoming this, one of the ways is to make Powtoon-assisted material and it will be even more interesting if the material is presented using the web. By utilizing the web, the material can be accessed anytime and anywhere. This development research employed a 4D development model up to the third stage, namely define, design, and develop. Research subjects were divided into 2 types namely, limited trial subjects and field trial subjects. The research instruments used were learning media validation sheets, student response questionnaires, and tests. The results of this study are (1) the developed learning media obtained the validity criteria of 82.00%. (2) The developed learning media obtained the practical aspects of 82.22% and for the field trials of 82.50% (3). The developed learning media obtained the effectiveness criteria in the limited trial of 83.33% and the field trial of 87.50%. Based on these results, it can be concluded that the learning media developed by researchers are appropriate for use in learning.